An NHC–Silyl–NHC Pincer Ligand for the Oxidative Addition of C−H, N−H, and O−H Bonds to Cobalt(I) Complexes. (27th January 2017) - Sun, Jian; Luo, Lun; Luo, Yi; Deng, Liang
Abstract: N‐Heterocyclic carbene based pincer ligands bearing a central silyl donor, [CSiC] −, have been envisioned as a class of strongly σ‐donating ligands that can be used for synthesizing electron‐rich transition‐metal complexes for the activation of inert bonds. However, this type of pincer ligand and complexes thereof have remained elusive owing to their challenging synthesis. We herein describe the first synthesis of a CSiC pincer ligand scaffold through the coupling of a silyl–NHC chelate with a benzyl–NHC chelate induced by one‐electron oxidation in the coordination sphere of a cobalt complex. The monoanionic CSiC ligand stabilizes the Co I dinitrogen complex [(CSiC)Co(N2 )] with an unusual coordination geometry and enables the challenging oxidative addition of E−H bonds (E=C, N, O) to Co I to form Co III complexes. The structure and reactivity of the cobalt(I) complex are ascribed to the unique electronic properties of the CSiC pincer ligand, which provides a strong trans effect and pronounced σ‐donation.